2021
DOI: 10.3390/textiles1020011
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fe3O4-PVDF Nanofiber Composite Mats for Cryogenic Magnetic Sensor Applications

Abstract: Magnetically responsive, mechanically stable and highly flexible iron (III) oxide-polyvinylidene fluoride (Fe3O4-PVDF) piezoelectric composite fiber mats were fabricated via one step electrospinning method for magnetic sensing at cryogenic temperature. The properties of Fe3O4-PVDF composite fiber mats were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, d33 and magnetization test. The fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Moreover, agglomerations of magnetite nanoparticles were detected in the beads using SEM and EDX spectra. Similar to our previous studies [5,22,27], larger amounts of magnetite are detected in the beads than in the nanofibers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, agglomerations of magnetite nanoparticles were detected in the beads using SEM and EDX spectra. Similar to our previous studies [5,22,27], larger amounts of magnetite are detected in the beads than in the nanofibers.…”
Section: Discussionsupporting
confidence: 90%
“…In this case, the beads The magnetic properties of nanofibers and nanofiber composites are of great interest and the morphology has an influence on the mechanical and chemical properties of the final nanofiber mats. The strategies for an optimal distribution of magnetic nanoparticles are discussed in the literature and various approaches are proposed, such as coating of particles or ultrasonication [20][21][22]. The study by Lalatonne et al notes that conventional mixing methods contribute to particles connecting and aggregating during the formation of the materials due to magnetic dipole and van der Waals interactions [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, after the addition of the Fe 3 O 4 particles in the polymer matrix, the intensity of the peak at 13.6° decreased, which was ascribed to inhibition of the polymer crystallization process caused by the magnetic particles decreasing the volume fraction of the crystalline phase in the fibers [ 35 , 46 ] (for more details please address to the DSC section of this study). Thus, submicron-sized Fe 3 O 4 particles strongly affect the structure of PHB, changing the rate of polymer crystallization, polymer chains mobility and thus limiting the growth of lamellas [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electrospinning has also been shown to mechanically pull the fibers due to the Taylor cone stretching and elongating during the process, further improving piezoelectricity [159]. Chowdhury et al compared the values of d 33 , a piezoelectric coefficient describing how efficiently the material can convert electrical energy to mechanical energy [164]. It was found that electrospun PVDF fiber having a fiber diameter of 105 nm has a significantly higher d 33 value (32 pC/N) as compared to that of PVDF pellet (5 pC/N), demonstrating the potential of electrospinning on the enhancement of the piezoelectric property.…”
Section: Piezoelectric Polymeric Scaffoldsmentioning
confidence: 99%